Prefabulous world : energy-efficient and sustainable homes around the globe - Koones, Sheri, 1949- (Abrams, 2014)
This book presents an international look at sustainable home design, it explores a compelling range of design styles and cutting-edge green technologies. The rising cost of fuel and the growing commitment to protect the environment have sparked exciting innovations in prefab home construction around the world. Showcasing many of the unlimited possibilities offered by prefabrication to build incredibly energy-efficient homes, Prefabulous World features fifty sophisticated examples of eco-friendly home design around the globe. With detailed floor plans, multiple gorgeous images of the exterior and interior of each home, and an extensive resource section listing architects, builders, and suppliers, this book is a vibrantly illustrated yet practical guide that reveals how living in a beautiful, well-built, energy-efficient home is achievable for us all, no matter where we live.